PREDIKSI KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH PDAM DI KECAMATAN LUBUK BEGALUNG KOTA PADANG TAHUN 2027 - Irma, Irma Sapitri; Purwaningsih, Endah (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Abstract The purpose of this research is: 1) To determine the population projection in Lubuk Begalung District in the year 207. 2) To ascertain the demand for clean water in Lubuk Begalung District based on the projected population increase over the next 10 years.The research design employed in this study is Quantitative Descriptive. The data utilized consists of secondary data and secondary data encompassing population figures, PDAM customers, and clean water availability data in Lubuk Begalung District. The analytical technique employed includes the Population Projection Method, specifically the Arithmetic Method, to predict the population, along with the prediction of clean water demand in the year 2027.The outcomes of this study reveal that Lubuk Begalung District is experiencing a significant increase in population and is categorized as a